Peningkatan Hasil Belajar Matematika Menggunakan Alat Peraga Melalui Metode STAD - Putrini R Harahap, Saima; Nasrawati, Nasrawati (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2024)
Teaching aids are basically tools used to illustrate concepts to students, thus facilitating their understanding of the subject matter. The purpose of this study was to determine the effectiveness of flat building props and the STAD method in facilitating mathematics learning of grade IV students at SDN 030 Tanese, Pao-Pao Village, Tutar District. The participants of this study were grade IV students (nine people) in the even semester of the 2023-2024 school year. The research was conducted at SDN 030 Tanese, Alu District, Polewali Mandar Regency, from 6 May 2020 to 18 May 2024. This type of research is known as Classroom Action Research (PTK), which requires teachers to implement various strategies to improve learning outcomes. These strategies may not be optimal, but they are designed to ensure that learning objectives are achieved. PTK aims to assist teachers in identifying effective strategies to facilitate student learning in the classroom. This study showed that students showed an improvement in their mathematics ability, as evidenced by an increase in the average score and the proportion of students who achieved a passing score. At the initial stage of the study, the students' average score was 75.7, with 77.3% of the students achieving a passing score. In the second cycle, the students' average score was 80.5, with 90.9% of the students passing. In conclusion, these findings suggest that the integration of teaching aids with the STAD method can facilitate improved mathematics learning outcomes for students at SDN 030 Tanese